2005
DOI: 10.1038/sj.embor.7400586
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of protein folding in extracellular space

Abstract: The pathologies of many serious human diseases are thought to develop from the effects of intra-or extracellular aggregates of non-native proteins. Inside cells, chaperone and protease systems regulate protein folding; however, little is known about any corresponding mechanisms that operate extracellularly. The identification of these mechanisms is important for the development of new disease therapies. This review briefly discusses the consequences of protein misfolding, the intracellular mechanisms that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 49 publications
2
104
0
Order By: Relevance
“…The Aβ peptide 1-42 (Aβ42) was purchased from Anaspec (USA), dissolved in 60 μL of 1.0 % NH 4 OH and brought to a final concentration of 250 μM using MilliQ water. This stock solution was separated into aliquots and stored at −80 °C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aβ peptide 1-42 (Aβ42) was purchased from Anaspec (USA), dissolved in 60 μL of 1.0 % NH 4 OH and brought to a final concentration of 250 μM using MilliQ water. This stock solution was separated into aliquots and stored at −80 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…), native proteins can misfold via partially structured intermediates to either disordered amorphous aggregates or ordered amyloid fibrils [3]. Amorphous aggregation occurs by a relatively fast and random process [4][5][6], whereas amyloid fibril formation occurs in a more ordered manner at a slower rate [7]. Protein misfolding which results in aggregate formation can lead to serious biological consequences.…”
Section: Introductionmentioning
confidence: 99%
“…[3] We found that the sequences of extracellular proteins have higher intrinsic aggregation propensity than intracellular ones, an observation that has been related to the dilution that occurs upon secretion. [19,20] We also found that disulfide bonds are associated with sequences of high aggregation propensity (Figure 3 g), which suggests that disulfide bonds have co-evolved with protein sequences [21] to minimize their propensity to form potentially toxic amyloid aggregates. This analysis would explain the high prevalence of disulfide bonds in extracellular proteins, where additional protective mechanisms that reduce misfolding and its consequences are likely to play a less significant role than inside the cell.…”
Section: Angewandte Chemiementioning
confidence: 83%
“…This analysis would explain the high prevalence of disulfide bonds in extracellular proteins, where additional protective mechanisms that reduce misfolding and its consequences are likely to play a less significant role than inside the cell. [20,22] The disulfide bonds of lysozyme inhibit the aggregation of this protein into amyloid fibrils by stabilizing the folded state-a fact that can be attributed to the reduction in the entropy of the unfolded state. [11] A partially unfolded state can nevertheless be populated as a result of changes in conditions, as in this work, or by mutations, as in patients with nonneuropathic systemic amyloidosis.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Based on these and other findings, it has been proposed that CLU forms part of an extracellular protein quality control system that helps to maintain proteostasis [72]. The CLU gene has been identified as an important risk locus for Alzheimer's disease.…”
Section: Chaperone Activity and Proteinase Inhibitionmentioning
confidence: 99%